From ocean to cage: evaluating the culture feasibility of Black-spotted croaker (Protonibea diacanthus) - Ghosh, Shubhadeep; Dash, Gyanaranjan; Dash, Biswajit; Pradhan, Rajesh Kumar; Megarajan, Sekar; Behera, Pralaya Ranjan; Ranjan, Ritesh; Sen, Swatipriyanka; Das, Madhumita; Suresh, Vettath Raghavan; Gopalakrishnan, Achamveetil; Jena, Joykrushna (Frontiers in Marine Science, 2025)
IntroductionThis study evaluates the feasibility of culturing the high-value marine fish Protonibea diacanthus in a polyculture system with Indian pompano (Trachinotus mookalee) using a marine cage culture setup. The study aims to determine growth performance, feed efficiency, and the potential of P. diacanthus as a candidate species for polyculture.MethodsWild-caught P. diacanthus were reared in six high-density polyethylene sea cages (Inner Diameter: 6 m; Outer Diameter: 7 m; Depth: 4.5 m; Area: 28.29 m²; Volume: 127.29 m³). Two experimental groups were established: Group-1 with 90 individuals (average weight: 130.15 ± 6.39 g) and Group-2 with 90 individuals (average weight: 287.80 ± 16.90 g). Each group was divided into three cages (30 fish/cage) and reared in triplicate with T. mookalee (2,500 fish/cage, average weight: 31.12 ± 1.17 g). The fish were cultured for 148 days and fed a commercial diet (40% crude protein, 10% crude lipid). Growth indices and feed efficiency indices were analyzed, and growth of the fish was modeled using von Bertalanffy Growth Function (VBGF).ResultsGrowth performance indices, including total length gain, body weight gain, and specific growth rate, were significantly higher in Group-1 (P ≤ 0.05). Feed efficiency indices (feed conversion ratio, feed efficiency ratio, and protein efficiency ratio) did not differ significantly between the groups (P > 0.05). VBGF modeling estimated P. diacanthus asymptotic length (L∞) at 164.21 ± 3.58 cm, asymptotic weight (W∞) at 44,070.19 ± 2811 g, growth coefficient (K) at 0.30 ± 0.01 yr−1 and t₀ at -0.005 ± 0.02 yr. The growth performance index (ϕ’) was calculated at 1.91, surpassing values reported for wild populations. Polyculture with P. diacanthus did not significantly affect the growth or feed utilization of T. mookalee (P > 0.05).Discussion and conclusionThe results indicate that P. diacanthus exhibits superior growth under marine cage culture conditions, with a high growth performance and compatibility in polyculture systems. These findings support the potential of P. diacanthus as a viable candidate for integration into commercial polyculture systems.